Effect of brief thermal aging on stress corrosion cracking susceptibility of LDSS 2101 in the presence of chloride and thiosulphate ions. (January 2018) - Zanotto, F.; Grassi, V.; Balbo, A.; Monticelli, C.; Melandri, C.; Zucchi, F.
Highlights: Study of the effect of brief-time aging within 650 ÷ 850 °C on LDSS 2101 SCC resistance. Thermal aging determined precipitation of chromium carbides and especially nitrides. LDSS 2101 was susceptible to SCC in NACE TM-0177 without/with S2 O3 2− ions. SCC susceptibility in the presence of S2 O3 2− increased after thermal aging. Interstitial nitrogen impoverishment negatively affected SCC susceptibility. Abstract: In this paper, the effect of brief aging within the 650–850 °C temperature range on the resistance of lean duplex stainless steel (LDSS) 2101 to stress corrosion cracking (SCC) was discussed. The thermal aging induced a decrease in Vickers microhardness and an increase in alloy ductility. This behaviour was connected to depletion of interstitial nitrogen in austenite. LDSS 2101 was found to suffer SCC in NACE TM-0177 solution, particularly under specific thermal aging and in the presence of thiosulphate ions (S2 O3 2− ) at 10 −4 and 10 −3 M. Crack nucleation and propagation were linked to microstructural variations connected to thermal aging.